PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Sunandar Sunandar (Universitas Negeri Malang, 2016)
The Influences of CTL Teaching-learning on the Learning Achievement of Primary School Students. The main purpose of this study was knowing whether using Contextual Teaching and Learning (CTL) approach was more effective than Textual Teaching and Learning (TTL) approach in mathematics study. The samples of this study were 85 students from class VA and VB of Ngesrep 01/02 Elementary School at Semarang. The instruments in this study were (1) learning achievement test (2) observation sheet of students activity (3) observation sheet of teachers activity. The result of this study are (1) the mathematics learning result especially at fraction topic of student with CTL instruction approach is at good level; (2) the mathematics learning result especially at fraction topic of student with TTL instruction approach is at middle level; (3) teacher teaching activity especially at fraction topic by CTL is good; (4) the mathematics learning result of students with CLT instruction approach is higher than the mathematics learning result especially at fraction topic of student with TTL instruction approach.